PENERAPAN MODEL PEMBELAJARAN CURAH PENDAPAT (BRAINSTORMING) DALAM MENINGKATKAN BUDAYA BELAJAR AKTIF SISWA - Sriwijayanti, Ribut Prastiwi; Daryono, Daryono; Hakim, Alimul (Jurnal Likhitaprajna, 2019)
Research problem is caused the lack of effectiveness of teaching ability of an educator in the process learning in Islamic Junior High School Wonomerto KedungSupit Wonomerto which implicates the learner's participation in developing the potential of a student. This studies aims to the describe application of learning models from brainstorming learning in improving learning culture of active learners. The subjects include, principal, homeroom, subject teachers, learners. Collection data techniques used observation, interview, and documentation. Analysis techniques use reduction, presentation, and conclusion/verification. From results of research, it is found that in application of Brainstorming model learning can improve the active learning culture of the students. With the implementation of this learning model the learners are more active again, in accordance with the learning steps ranging from preliminary activities, kegian tan core, until closing activities. But this Brainstorming learning model needs to be re-developed and integrated with other learning models so as achieve learning objectives that has been conceptualized. Keywords: application, brainstorming, learning model, learning culture